Hydrogenase-based nanomaterials as anode electrode catalyst in polymer electrolyte fuel cells - Tsuda, Muneyuki (Animo Repository, 2005)
We consider hydrogenase-based nanomaterials for possible use as anode electrode catalysts in polymer electrolyte fuel cells (PEFCs). We choose Fe-only hydrogenase component of Desulfovibrio desulfuricans (DdHase) as a hydrogenase complex, and investigate its catalytic activity for H2 dissociation using ab initio calculations based on density functional theory (DFT). We found two possible H-H bond cleavage pathways, which are heterolytic and possess low activation barriers. Moreover, the H2 dissociation can be promoted by inducing spin polarization of the H2 adduct. We report that hydrogenase or hydrogenase-based nanomaterials can manipulate to exhibit the catalytic activity equivalent to the well-known platinum catalyst. © 2004 Elsevier Ltd. All rights reserved.